The Resilience of Older Adopted Children: Their Perspective on Challenges and Facilitators - Anca Bejenaru; Mihai-Bogdan Iovu; Sergiu-Lucian Raiu (SAGE Open)
Since 2016, the adoption of older children has become a priority for policymakers and practitioners in Romania. Until 2022, no study gave a voice to Romanian children to understand how they experience adoption and the challenges and facilitator factors they face. This study aimed to fill this gap by interviewing 12 preadolescents, domestically adopted. They offered important insights into the challenges they faced before and during adoption and the tasks they had to undertake after the process. They also highlighted the factors that facilitated their resilience. We found that older children, despite their past adversities, demonstrate good resilience, reflected in their ability to create new bonds with their adopters, self-satisfaction, and awareness of the progress they have made after adoption, and their confidence and future aspirations. Based on the interviews, we formulated recommendations for practice and policies.